La última palabra en dosis mínima - Fernandes, César Eduardo [UNESP]; De Azevedo, Lucía Helena; Stephan, Cristina; De Souza Ferreira, José Arnaldo; De Melo, Nilson Roberto; Peixoto, Sergio (My University, 2005)
In this article we rewiewed the indications of the low-dose hormone replacement therapy in post menopausal women. We evaluate the effects of this therapy on menopausal symptoms bone metabolism, cardiovascular risk and endometrial cancer. The low-dose hormone replacement therapy is satisfactory to relief menopausal symptoms and improves lipid profile preventing atherosclerosis. It does not increase the risk of hyperplasia or endometrial cancer when is associate with progestagens. The low dose hormone replacement therapy is also associate to improve bone mineral density but to have better comprehension about the effective action of the low dose hormone replacement therapy on bone, more studies evaluating the risk of fractures are necessary.
Final word on minimum dose
Keywords: Bone metabolism; Cardiovascular risk; Endometrial cancer; Low dose; Menopausal symptoms; gestagen; atherosclerosis; bone metabolism; cardiovascular risk; endometrium cancer; hormonal therapy; human; hyperplasia; low drug dose; menopausal syndrome; postmenopause; review